2015
DOI: 10.1177/0148607115570695
|View full text |Cite
|
Sign up to set email alerts
|

A Reproducible and Individualized Method to Predict Osmolality of Compounded Pediatric Parenteral Nutrition Solutions

Abstract: Our model predicted osmolality accurately and may be used in routine practice in any setting once adapted to the local production practice. Approximations by osmolarity severely underestimate actual osmolality. Keeping osmolarity <800 mOsm/L seems sufficient to ensure that actual osmolality does not exceed 1000 mOsm/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 24 publications
2
11
1
Order By: Relevance
“…However, one study suggested that the commonly used estimation method may underestimate the true osmolality of compounded formulations. Although a new predictive method has been proposed, it requires additional research to validate its accuracy 20 . When peripheral PN use is necessary, the intravenous site must be monitored frequently for signs of phlebitis.…”
Section: Question 6: In Which Patients Is Peripheral Pn a Reasonable mentioning
confidence: 99%
“…However, one study suggested that the commonly used estimation method may underestimate the true osmolality of compounded formulations. Although a new predictive method has been proposed, it requires additional research to validate its accuracy 20 . When peripheral PN use is necessary, the intravenous site must be monitored frequently for signs of phlebitis.…”
Section: Question 6: In Which Patients Is Peripheral Pn a Reasonable mentioning
confidence: 99%
“…Since osmolality can only be measured after the solution is mixed, it is impractical to determine in practice, and therefore the calculated osmolarity, a theoretical value, is used to approximate the compounded PN osmolality. Preliminary studies in Europe and this study suggest that calculated osmolarity (mOsm/L) underestimates osmolality (mOsm/kg), determined by direct measurement, in individually compounded PN solutions administered to NICU patients . Furthermore, these findings raise the possibility that prior clinical studies may have incorporated an underestimate of PN osmolality, thereby introducing a systematic bias in the existing literature on this topic.…”
Section: Clinical Relevancy Statementmentioning
confidence: 64%
“…Risk of peripheral IV infiltration increases at higher levels of infusion osmolality, accounting for 23%–78% of complications related to PN administration in neonates . Probability of infiltration is likely a function of many factors, in addition to osmolality of the PN solutions . PN osmolality (mOsm/kg) is typically estimated from calculated osmolarity (mOsm/L) using preset manufacturer algorithms that reflect local solution composition .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations